A configuração urbana e sua relação com os microclimas: estudo de frações urbanas na cidade de Maceió - Almeida, Eveline Maria de Athayde (2006)
The present study analyzes the relationship between urban configuration and local microclimates variations in two urban areas in the city of Maceió AL. The analysis identifies some aspects of urban form as densely built areas, pavement soil and green areas at the studied area. Two transepts are established and several points are selected for measurements of relative humidity, air temperature and wind velocity during the month of January 2005. Those measurements show the strong contribution of urban form characteristics in the air temperature and humidity values. The results indicate the effects of the urban occupation on the development of microclimates. The purpose is, thus, to confirm the importance of microclimate analysis as an important tool for urban planning; especially aspects related with the urban configuration of Maceió and urban discomfort.